2004
DOI: 10.1037/0003-066x.59.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Research Online: Report of Board of Scientific Affairs' Advisory Group on the Conduct of Research on the Internet.

Abstract: As the Internet has changed communication, commerce, and the distribution of information, so too it is changing psychological research. Psychologists can observe new or rare phenomena online and can do research on traditional psychological topics more efficiently, enabling them to expand the scale and scope of their research. Yet these opportunities entail risk both to research quality and to human subjects. Internet research is inherently no more risky than traditional observational, survey, or experimental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
621
1
20

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 797 publications
(652 citation statements)
references
References 49 publications
10
621
1
20
Order By: Relevance
“…Despite former preconceptions, evidence is accumulating that online studies can provide valid data for research on implicit associations (Nosek, Banaji, & Greenwald, 2002), personality (Gosling, Vazire, Srivastava, & John, 2004), and sexuality (Mustanski, 2001). The study was implemented in line with the guidelines on Internet research proposed by Michalak and Szabo (1998) and the recommendations given by Kraut, Olson, Banaji, Bruckman, Cohen, and Couper (2004). After basic demographic questions, the sociosexuality IAT was given, followed by, among other measures, the Sociosexuality Scale.…”
Section: Methods: Internet Iat Studymentioning
confidence: 99%
“…Despite former preconceptions, evidence is accumulating that online studies can provide valid data for research on implicit associations (Nosek, Banaji, & Greenwald, 2002), personality (Gosling, Vazire, Srivastava, & John, 2004), and sexuality (Mustanski, 2001). The study was implemented in line with the guidelines on Internet research proposed by Michalak and Szabo (1998) and the recommendations given by Kraut, Olson, Banaji, Bruckman, Cohen, and Couper (2004). After basic demographic questions, the sociosexuality IAT was given, followed by, among other measures, the Sociosexuality Scale.…”
Section: Methods: Internet Iat Studymentioning
confidence: 99%
“…There is an ongoing controversy concerning the comparability of Internet samples and face-to-face samples. Naturally, online participants tend to be self-selected (Kraut et al, 2004). However, in their review, Gosling, Vazire, Srivastava, and John (2004) concluded that Internet users do not differ from nonusers SBEH 400165-2/6/2009--340026---SBEH own Style on markers of adjustment and depression.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, online surveys are very appealing for research and industry consultation because they achieve potential sample sizes larger than other methods, they are faster, more cost-effective and provide a high degree of automation of the experiment (Reips, 2002;Kraut et al, 2004). However, online surveying also has some limitations, including those discussed above as well as design methodological issues (Reips, 2002;Kraut et al, 2004), which researchers have to carefully consider when employing them.…”
Section: Discussionmentioning
confidence: 99%
“…However, online surveying also has some limitations, including those discussed above as well as design methodological issues (Reips, 2002;Kraut et al, 2004), which researchers have to carefully consider when employing them. One option for Farmer Institutions to overcome the online surveys limitations regarding representativeness and avoiding overwhelming farmers with too much e-mailing, would be to form a constant representative sample of the farmer population which would be periodically surveyed to monitor and research issues of industry interest.…”
Section: Discussionmentioning
confidence: 99%